p‑Bromophenol-Enhanced Bienzymatic Chemiluminescence Competitive Immunoassay for Ultrasensitive Determination of Aflatoxin B1 - Li, Juan; Zhao, Xu; Chen, Li-Jian; Qian, Hai-Long; Wang, Wen-Long; Yang, Cheng; Yan, Xiu-Ping (Analytical chemistry (Washington), 2019)
Aflatoxin B1 (AFB1) contamination is one of the most critical global issues in food safety. The high carcinogenic nature necessitates rapid and specific methods for the determination of AFB1 in foodstuffs at ultratrace levels. Here, we report an enhanced bienzymatic chemiluminescence competitive immunoassay for ultrasensitive and high-throughput determination of AFB1. In this assay, protein G was first coated on the wells of a microplate for recognizing the Fc fragment of anti-AFB1 mAbs to reduce the antibody dosage and guarantee high immunological reaction efficiency. The target AFB1 competed with glucose oxidase labeled AFB1 for the limited anti-AFB1 mAbs in the wells of the microplate. p-Bromophenol was employed as an enhancer to obtain intense and long-lasting chemiluminescence. The utilization of an enhancer and bienzymatic catalysts effectively improved the detection sensitivity. The developed method offered a good linearity over 5 orders of magnitude, a detection limit of 5 pg L–1, and a relative standard deviation of 1.9% for AFB1. The application of the developed method to the analysis of grain samples gave quantitative recoveries from 94.0% to 97.0%. The developed method provides a universal platform for high-throughput, ultrasensitive, and high specific detection of pollutants or nutrients in foods.